Elective neck dissection versus observation in patients with head and neck cutaneous squamous cell carcinoma. Issue 23 (6th August 2021) - Amit, Moran; Liu, Chuan; Mansour, Jobran; Gleber‐Netto, Frederico O.; Tam, Samantha; Baruch, Erez N.; Aashiq, Mohamed; El‐Naggar, Adel K.; Moreno, Amy C.; Rosenthal, David I.; Glisson, Bonnie S.; Ferrarotto, Renata; et al.
Abstract : Background: The survival benefit of elective neck dissection (END) for patients with cutaneous squamous cell carcinoma (cSCC) of the head and neck and no evidence of regional metastasis (cN0) has never been reported. The aim of this study was to determine the effect of END on patient survival. Methods: The authors included patients with head and neck cSCC who had undergone primary surgery from 1995 to 2017. The primary end point was survival, and the secondary end points were the incidence of occult regional disease and regional disease control. To assess the impact of END on survival, the authors used multivariable Cox proportional hazards models with propensity score and matching techniques for internal validation. Results: A total of 1111 patients presented with no evidence of nodal disease; 173 had END, and 938 were observed. Adjuvant radiotherapy to the neck was administered to 101 patients (9%). END resulted in a 5‐year overall survival rate of 52%, whereas the rate was 63% in the observation group ( P  = .003 [log‐rank]). The 5‐year disease‐free survival rate for patients undergoing END was similar to that for the observation group (73% vs 75%; P  = .429). A multivariate regression model showed that the performance of END was not associated with improved rates of overall, disease‐specific, or disease‐free survival; similarly, among patients with advanced disease (T3‐4), those who underwent END did not have improved survival rates. Conclusions: Among patients with cSCC of the head and neck, observation of the neck nodes resulted in noninferior survival rates in comparison with END at the time of primary surgery. Further studies are required to elucidate the role of END in patients with advanced disease. Abstract : Among patients with cutaneous squamous cell carcinoma of the head and neck, observation of the neck nodes results in similar survival rates in comparison with elective neck dissection at the time of primary surgery.